Exploring Intervention Strategies for Effective Integration of Indigenous Games in Teaching Market Structures in Economics Class in Thabo-Mofutsanyane Education District, Free State, South Africa - Molise, Habasisa; Mamabolo, Moketla; Modiba, Ngoako (Journal of Research, Innovation, and Strategies for Education (RISE), 2026)
The teaching of market structures is often hindered by learners’ difficulty in understanding abstract concepts, and while indigenous games offer a culturally relevant, experiential approach, their classroom use remains inconsistent. This study addresses this gap by exploring context-specific intervention strategies for effectively integrating indigenous games in rural Economics classrooms. Guided by the interpretivist paradigm and a qualitative case study design, data were generated through semi-structured interviews with six purposively selected Economics teachers from three rural schools in the Thabo-Mofutsanyane Education District. Thematic analysis was employed to analyse participants’ narratives. The findings revealed that although teachers value indigenous games such as Morabaraba, Kgati, and Diketo for promoting learner engagement and contextual understanding, their implementation is constrained by systemic challenges. Two key intervention needs emerged: the development of structured teaching guidelines and the provision of targeted professional development. Teachers highlighted the absence of curriculum-aligned frameworks, lesson exemplars, and assessment tools, resulting in fragmented pedagogical practices. Additionally, limited training restricted their ability to translate gameplay into structured economic instruction. The study concludes that institutionalising indigenous game-based pedagogy requires curriculum integration, policy recognition, and sustained teacher capacity-building initiatives. This study contributes to existing literature by moving beyond descriptive accounts of indigenous games to provide empirically grounded, context-specific intervention strategies for their structured integration in rural Economics classrooms.